The Effect of Ecoenzyme on Plant Height and Leaf Number of Kangkung (Ipomoea reptans Poir) Hydroponically Cultivated - Amalia Fildzah Sharfina; Resti Fevria (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Kale is a widely popular cultivated plant. One of the ways to cultivate kale is by using a hydroponic system. Hydroponic systems usually use inorganic chemical nutrients such as AB mix. As an alternative to suppress the use of inorganic fertilizers, liquid organic fertilizers are used, namely ecoenzyme. Ecoenzyme is a liquid extract from the fermentation of organic kitchen waste with a sugar substrate (brown sugar or cane sugar) added with water.This study aims to determine the influence of ecoenzyme on the height and number of leaves of kale plants cultivated hydroponically. This study is an experimental study with 5 treatments and 5 repetitions consisting of P1 (control), P2 (2 mL ecoenzyme + 1 L water), P3 (3 mL ecoenzyme + 1 L water), P4 (4 mL ecoenzyme + 1 L water), and P5 (5 mL ecoenzyme + 1 L water). The data obtained is analyzed with a variety of fingerprints (ANOVA) with a 5% DMRT Advanced Test. The results obtained from research that ecoenzyme affects the number of kale leaves with the highest average of 14.6 strands (P4).